QoE Aware Resource Allocation for Video Communications over LTE Based Mobile Networks - Ryan Perera; Anil Fernando; Thanuja Mallikarachchi; Hemantha Kodikara Arachchi; Mahsa Pourazad (EAI Endorsed Transactions on Cloud Systems, 2016)
As the limits of video compression and usable wireless radio resources are exhausted, providing increased protection to critical data is regarded as a way forward to increase the effective capacity for delivering video data. This paper explores the provisioning of selective protection in the physical layer to critical video data and evaluates its effectiveness when transmitted through a wireless multipath fading channel. In this paper, the transmission of HEVC encoded video through an LTE-A wireless channel is considered. HEVC encoded video data is ranked based on how often each area of the picture is referenced by subsequent frames within a GOP in the sequence. The critical video data is allotted to the most robust OFDM resource blocks, which are the radio resources in the time-frequency domain of the LTE-A physical layer, to provide superior protection. The OFDM resource blocks are ranked based on a prediction for their robustness against noise. Simulation results show that the proposed content aware resource allocation scheme helps to improve the objective video quality up to 37dB at lower channel SNR levels when compared against the reference system, which treats video data uniformly. Alternatively, with the proposed technique the transmitted signal power can be lowered by 30% without sacrificing video quality at the receiver.